Human Factors Before Digital HR: A Case from the Furniture Industry - Agustin, Zhenia; Sumastuti, Efriyani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The This study investigates the influence of key human factors—namely work motivation, work discipline, work environment, job satisfaction, and work stress—on employee performance at CV Dijawa Abadi, a furniture manufacturing company. Using a quantitative approach, data were collected from 141 employees through a structured Likert-scale questionnaire and analyzed using multiple linear regression. The findings reveal that all five independent variables have a positive and significant effect on employee performance. These results highlight the importance of understanding traditional human resource dynamics in organizations that have not yet transitioned to digital HR systems. The study provides valuable insights for companies in the furniture industry and similar labor-intensive sectors, offering a foundational understanding to support future implementation of digitally integrated HR strategies.